Attitudes of Chinese Malaysian University students towards Agape love in selected German fairy tales - Lee, Soo Li (2015)
Engaging with two selected Grimm’s fairy tales (1812), The Fisherman and His Wife and The Three Snake-Leaves, the current study examined Chinese Malaysian university students’ attitudes toward love by applying Love Attitudes Scale (Hendrick & Hendrick, 1986). Love Attitudes Scale was developed according to Lee’s (1973/1976) six basic love styles (Eros, Ludus, Storge, Mania, Pragma and Agape). With this love scale, only Agape subscale was used to investigate the Chinese Malaysian university students. The specific objectives of the study are: (a) to identify the love style in selected German fairy tales by using textual analysis; (b) to examine attitudes toward love among Chinese Malaysian university students; and (c) to gauge the love attitudes of Chinese Malaysian university students towards the characters depicted in selected Grimm’s fairy tales. In this study, the results were discussed based on eight focal points: (a) the readiness to sacrifice for love; (b) the readiness to remain loyal to the lover; (c) the readiness to accept the lover’s weakness; (d) the readiness to improve the lover; (e) the readiness to protect the lover; (f) the readiness to maintain the relationship; (g) the readiness to experience similar relationship; and (h) the similarity to current relationship in Malaysia. A questionnaire survey of forty-eight undergraduate and postgraduate students was conducted in a Malaysian public university. Participants were presented with the two selected German literary texts in English before filling up questionnaires consisting of fourteen items in each (for each selected fairy tale) with revised items (adapted from Love Attitudes Scale). The questionnaires focused on the assessment of participants’ opinions about the depicted romantic relationship between men and women in the selected texts. Regarding the first objective, results of textual evidence indicated that The Fisherman and His Wife and The Three Snake-Leaves emphasize the love style of Agape. Regarding the second objective, the findings showed significant love attitudes of Chinese Malaysian university students: their mind seems to be agapic in dealing with romantic relationship. Regarding the third objective, the similarities of attitudes toward love were found between Chinese Malaysian university students and the characters depicted in selected Grimm’s fairy tales. Similarly, the differences of attitudes toward romantic relationship were also found between Chinese Malaysian university students and the depicted characters. However, the number of similarities between Chinese Malaysian university students and the depicted characters (participants would act as the characters did) is nearly equal with the number of differences between Chinese Malaysian university students and the depicted characters (participants would not act as the characters did) in relation to attitudes toward romantic relationship. In other words, both selected Grimm’s fairy tales only received partial acceptance from Chinese Malaysian university students. The “agapic view of love” is suggested to be a construct uniquely defined within the culture of Chinese Malaysians. In sum, this study may not only suggest structures and practices of Chinese Malaysian’s culture in terms of love attitudes, but also contribute to a better understanding of the German literature. This and similar studies help to understand the social values among different cultures as well as to avoid disappointment and misunderstanding in romantic relationship of mixed cultures.